In-situ TEM observation of rock salt crystal precipitation in liposome. Issue 25 (21st April 2016) - Ai, Haruka; Moriya, Naoto; Ube, Takuji; Harumoto, Takashi; Arai, Yoshihiro; Murata, Kazuyoshi; Ishiguro, Takashi
ABSTRACT: Liposome reinforced by adding cholesterol was synthesized using the dipalmitoyl-phosphatidylcholine (DPPC). Phase stability of the phospholipid bilayers was examined by FT-IR spectroscopy. The reinforced liposomes filled with ultrapure water or physiological saline were observed by the conventional TEM equipped with a mass spectrometer. It was confirmed that the liposomes filled with water or saline solution were stable in the vacuum at room temperature. However, during electron irradiation, water molecules escaped gradually, and a single crystal of rock salt precipitated in the liposome.